Comparing Zirconium Crown Marginal Adaptation in Preparations with Two Different Occlusal Reductions - Ali Khekan; Bernd Kordaß (MDPI AG, 2024)
This study aimed to assess and contrast the effects on the vertical marginal fit of full contour CAD/CAM-generated monolithic zirconia crowns at pre- and post-cementation levels with various occlusal reduction schemes (planar and flat) and cements. Forty sound human maxillary first premolars were sampled for this study. The samples were divided into two main groups with twenty samples in each group according to the occlusal reduction scheme as follows: Group A included a chamfer finishing line design with a planar occlusal reduction scheme and Group B included a chamfer finishing line design with a flat occlusal reduction scheme. Each group was sampled into two subgroups (n = 10) based on the type of cement as follows: resin-modified glass ionomer cement (Fuji Plus) for subgroups A1 and B1, and a universal adhesive system (Duo Estecem II) for subgroups A2 and B2. Marginal gaps were tested in four indentations using a Dino light stereomicroscope (230×). Paired T-tests and Student's t-tests were used to analyze the data. Before cementation, subgroup A1 scored the lowest mean of vertical marginal gap values, while subgroup B2 scored the highest mean; following cementation, subgroup A1 scored the lowest mean of vertical marginal gap values, and subgroup B2 scored the highest mean of vertical marginal gap values. A chamfer finishing line design with a planar occlusal reduction scheme could be a preferable occlusal reduction scheme.